Seismic performance of exterior reinforced concrete beam-column joint with corroded reinforcement - Zhang, Xinchen (2022)
Corrosive environment adversely affects the durability of existing reinforced concrete (RC) structures as well as its performance under seismic loading. In this paper, the seismic behaviour of corroded reinforced concrete (RC) exterior joint was experimentally evaluated. Eight similar RC exterior joints with various corrosion level of reinforcements were tested under two levels of representative column axial force ratio. Lateral loading resisting, ductility, energy dissipation and stiffness of corroded specimens were examined and compared with uncorroded control specimens. Joint shear stress and the development length of beam longitudinal reinforcement were investigated and compared with available design code. In addition, the joint internal force flow of corroded joint was investigated analytically based on modified strut-and-tie model (STM). Experimental results indicate that corrosion of reinforcements have significant adverse effect on the strength and lateral drift capacity of the joints as well as other mechanical properties. Based on the STM model and parametric study, it is further found that the effect of corrosion level on joint stress level is more significant at higher axial force ratio. In addition, an axial force ratio above 0.2 is detrimental to the joint.